From Thermodynamics to Information: Landauer’s Limit and Negentropy Principle Applied to Magnetic Skyrmions - Zivieri, Roberto (Frontiers in Physics, 2022)
Magnetic skyrmions are topological swirling spin textures objects that can be manipulated and employed as information carriers. This is accomplished based either on their ground-state properties or their thermodynamic properties. Landauer’s principle establishes an irreversible conversion from information to physics. The inverse mechanism, the inverse mechanism is proposed for magnetic topological defects forming in magnetic nanostructures that are regarded as closed thermodynamic systems confirming Szilard’s and Brillouin’s hypotheses. This mechanism consists of the creation of bits of information using a thermodynamic source having a form of negentropy. In this perspective article, the following are proved for magnetic skyrmions: 1) Landauer’s principle expressed in terms of negentropy and 2) the generalized second principle of thermodynamics based on Brillouin’s negentropy principle of information. The thermodynamic entropy is converted into information entropy at the expense of negentropy, “negative entropy” corresponding to the loss of thermodynamic entropy from the magnetic skyrmion itself. A recently proposed practical device enables the verification of points 1) and 2) and allows a full understanding of the interchange between thermodynamics and information and vice versa regarding skyrmions as information units and showing, in perspective, the considerable advantages offered by this type of storing and coding information.